INTERPERSONAL COMMUNICATION AND FACILITATOR COMMUNICATION COMPETENCY ON EFFECTIVENESS OF THE SUPERIOR HIGHER EDUCATION UPBRIGING PROGRAM - Hesti, Sri; Mansur, Suraya (ASPIRATION Journal, 2023)
This study examines the impact of interpersonal communication and facilitators' communication competence on the effectiveness of the Superior Higher Education Upbringing Program at Universitas Mercu Buana. The research investigates three key variables: interpersonal communication, communication competence, and program effectiveness. Using a quantitative approach with survey methodology, the study analyzed data from program participants between 2017 and 2019. The findings reveal significant influences of both interpersonal communication and communication competence on program effectiveness, both individually and in combination. Specifically, interpersonal communication accounts for 53.3% of program effectiveness, while communication competence contributes 54.6%. Together, these two factors explain 57% of the program's effectiveness, with the remaining 43% attributed to other variables not examined in this study. Notably, the facilitators' motivational approach in the Superior Higher Education Program demonstrated the strongest correlation with participants' engagement in the Internal Quality Assurance System (SPMI), ultimately contributing to the development of a quality-focused culture at the university. This research highlights the crucial role of effective communication in educational program success and quality assurance implementation.